Older Adults With Hearing Loss Have Reductions in Visual, Motor and Attentional Functioning - Susan M. Gillingham; Susan M. Gillingham; Antonino Vallesi; Antonino Vallesi; M. Kathleen Pichora-Fuller; M. Kathleen Pichora-Fuller; Claude Alain; Claude Alain; Claude Alain; Claude Alain (Frontiers in Aging Neuroscience, 2018)
Evidence from epidemiological, laboratory and clinical research suggests a link between age-related auditory declines and domain-general cognitive declines. Nevertheless, few studies have experimentally compared measures of non-auditory cognitive functions in younger normal hearing adults (YN), older adults with typical hearing thresholds for their age (ONHA) and older adults with clinically significant threshold hearing loss (OHL). The current study investigated the differences between these groups on measures of attentional response selection and execution to visual stimuli. A visual reaction time (RT) paradigm involving four tasks with differing and hierarchical attentional demands was administered. RTs on trials with differing foreperiods (FPs; pre-stimulus waiting times) were analyzed to assess context-related slowing, error commission and related cognitive control and strategic and automatic neural preparatory processes. The OHL group demonstrated a general slowing that was most apparent on the simplest tasks. Although the number of errors was similar when comparing all three groups, the OHL group exhibited less control over recovery from an error compared to the younger and ONHA groups. Unlike the YN and ONHA groups, the OHL group also showed difficulties with both strategic and automatic response preparation, although automatic preparation was more affected across all tasks. This pattern of results suggests that in older adults with hearing loss there is an underlying difficulty in automatic temporal processing that can affect higher order cognitive functions, although there may not be a completely generalized decline in cognitive functioning that is associated with hearing loss.